Interaksi Sosial Anak Down Syndrome di TK Nusa Indah Jakarta - Ayuningrum, Desy; Afif, Nur (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
Down syndrome is one of the children with special needs, where the child has an intellectuallevel that is low or below average. This study aims to find out, provide an overview, and explainabout the forms of social interaction carried out by a child with special needs with Downsyndrome with teachers and friends in regular school. This is done in order to provide a trueview and picture of the social behavior that appears from children with Down syndrome, whereit has not been widely known by educators and the public. This research is a qualitative researchwith case study method, this research uses purposive sampling technique. This study uses onesubject with certain characteristics. Data collection techniques used are: non-participantobservation, interviews, questionnaires, and documentation. Data analysis techniques include:(1) data reduction (2) data presentation, and (3) conclusion drawing. The results of data collection conducted from January to March 2017, found that there are four forms of behaviorthat appear classified in social behavior and forms of behavior classified as asocial behavior.The intended social behaviors are friendly behavior, sympathetic behavior, cooperativebehavior, and competitive behavior. Existing asocial behaviors consist of resistance behaviorand attack behavior.